A lacustrine record of the early Aptian climate change by oceanic anoxic event (OAE) 1a in the Jiaolai Basin, Eastern China. (November 2020) - Zhang, Xiangyu; Li, Shoujun
Graphical abstract: Highlights: Laiyang Sag was influenced by an extreme dry and hot climate during the early Aptian. In the early depositional stage of the Shuinan Formation, the lake was relatively closed. The increase of paleosalinity was the consequence of influence of OAE 1a on Laiyang paleo-lake. Abstract: The early Aptian climate change resulted in changes in both the ocean and terrestrial ecosystems. This global climate change is well documented in marine sediments in the form of the oceanic anoxic event (OAE) 1a, but it has rarely been reported from the inland lakes in the East Asian continent. In this study, carbon and oxygen isotopes, quantitative palaeosalinity, clay mineral composition and contents, organic matter content, and detrital zircon ages from the Shuinan and Zhifengzhuang Formations in the Jiaolai Basin were determined to examine whether this global climate change was recorded in inland lakes. This study showed that in the early depositional stage of the Shuinan Formation, the paleo-lake in the Jiaolai Basin was a saline lake with long detention and strong sealing. The climate of the Jiaolai Basin became hotter and drier in the early Aptian ( 120 Ma) and the evaporation increased, which increased the palaeosalinity of the Shuinan Formation. High-salinity water, high temperatures, and strong evaporation led to a positive migration of the δ 13 C values. The extreme dry and hot climate documented in the black shale of the Shuinan Formation might serve as a response of inland lakes to OAE 1a. This study provided not only a lacustrine record of an Early Aptian global climate change event but also a new perspective to deepen the understanding of the effects of the Cretaceous climate change in terrestrial ecosystems.